Immunotherapeutic Strategies for Alzheimer's Disease Treatment - Beka Solomon (The Scientific World Journal)
Naturally occurring antibodies against amyloid-β peptides have been found in human cerebrospinal fluid and in the plasma of healthy individuals, but were significantly lower in Alzheimer's disease (AD) patients, suggesting that AD may be an immunodeficient disorder. The performance of anti-amyloid-β antibodies in transgenic mice models of AD showed that they are delivered to the central nervous system, preventing and dissolving amyloid-β plaques. Moreover, these antibodies protected the mice from learning and age-related memory deficits. Active and/or passive immunization against the amyloid-β peptide has been proposed as a method for preventing and/or treating AD. Immunotherapy represents fascinating ways to test the amyloid hypothesis and offers genuine opportunities for AD treatment, but requires careful antigen and antibody selection to maximize efficacy and minimize adverse events.